Penerapan Nilai Karakter dalam Pendidikan KMI Gontor: Analisis Prinsip Efektif Lickona (CEP) - Mujahada, Kharis Syuhud; Rohmatullah, Dawam Multazam (IIQ An Nur Yogyakarta, 2025)
This study analyzes the implementation of character values within the Kulliyatul Mu'allimin Al-Islamiyah (KMI) Islamic Boarding School Darussalam Gontor education system, based on the 11 principles of Effective Character Education as proposed by Thomas Lickona. Character education represents a critical aspect of contemporary educational systems, particularly in Islamic boarding schools (pesantren) that integrate Islamic traditions with modern educational approaches. Employing a qualitative methodology with a phenomenological approach, this study explores the in-depth experiences of various stakeholders involved in character education implementation. Data were collected through in-depth interviews, participant observations, and document analysis involving key informants such as kyai (Islamic clerics), ustaz (Islamic teachers), santri (students), and alumni of KMI Gontor. Findings indicate that the KMI Gontor education system effectively applies most of Lickona’s principles, particularly in fostering a caring community, cultivating students’ intrinsic motivation, and embedding ethical values within the academic curriculum. The study reveals that KMI Gontor’s holistic integration of Islamic values with modern character education principles successfully shapes students’ character across cognitive, affective, and behavioral domains. This research contributes to the advancement of a pesantren-based character education model that can be adapted by other educational institutions.